Free-Flowing Water, Restrained - Brian Obermeyer (Symphony in the Flint Hills, 2018)
Introduction: I suspect few think of the Flint Hills—an upland landscape with modest rainfall and occasional droughts—as an important area for free-flowing water. Surprisingly, though, it is.